Influence of age, stigma and social support on male temporary ejaculation failure on IVF oocyte retrieval day - Jinluan Wang; Mingyue Xue (BMC, 2021)
Abstract Objective To explore the social and psychological factors associated with male Temporary Ejaculation Failure (TEF) during In Vitro Fertilization (IVF), with the goal of providing a theoretical basis for clinical intervention and treatment. Methods The study included 75 TEF patients and 223 non-TEF patients undergoing IVF treatment at the center of reproduction and genetics of Integrated Chinese and Western medicine in the Affiliated Hospital of Shandong University of Traditional Chinese Medicine from May 2019 to May 2020. A questionnaire survey was then administered to the study subjects. The questionnaires included general information, Perceived Stress Scale (PSS), Stigma Questionnaire, Perceived Social Support Scale (PSSS), and Positive Psychological Capital Questionnaire (PPQ). Logistic regression analysis was then used to analyze the social psychological factors associated with the research objectives. Results Comparison of social demographic factors and clinical data between TEF group and non-TEF group: there were significant differences in the age and educational level between the two groups (P< 0.05), and the average age of the TEF group (37.01±7.11) was significantly higher than that of the non-TEF group (34.89±6.24). In addition, patients with high school or technical secondary school education levels had the lowest probability of TEF(X 2 =7.662, P=0.022). 2. The difference of related social and psychological factors between the two groups: the scores of perceived stress (17.57±6.51) and stigma (4.52±3.87) in the TEF group were significantly higher than those in the non-TEF group, which were (15.50±5.00, P< 0.05) and (2.61±3.52, P< 0.05), respectively. On the other hand, the scores of social support (55.31±14.04) and psychological capital (121.73±25.93) in the TEF group were significantly lower than those in the non-TEF group, which were (60.74±10.93, P< 0.05) and (130.31±17.32, P< 0.05), respectively. Results Obtained after conducting univariate logistic regression analysis indicated that age (OR=1.051, P=0.016), perceived stress (OR=1.073, P=0.005), stigma (OR=1.139, P< 0.001), family support (OR=0.901, P< 0.001), friend support (OR=0.932, P=0.023), other support (OR=0.915, P=0.004), self-efficacy (OR=0.947, P=0.009), resilience (OR=0.947, P=0.013), hope (OR=0.930, P=0.002), and optimism (OR=0.953, P=0.032) can all significantly affect male TEF.4. Moreover, the multivariate logistic regression analysis results indicated that age (OR=1.071, P=0.002) and stigma (OR=1.132, P=0.003) can positively predict TEF, while family support (OR=0.877, P=0.012) can negatively predict TEF. Conclusions The results obtained in this study have indicated that age and stigma are independent risk factors for male TEF, while family support is a protective factor of TEF. Analyzing the treatment of TEF from a socio-psychological perspective provides a new intervention target for effectively reducing its incidence, thereby helping to improve the success rate of IVF.